2020
DOI: 10.2147/dmso.s278542
|View full text |Cite
|
Sign up to set email alerts
|

<p>Metabolic Syndrome and 5-Year Incident Hyperuricemia Among Older Chinese Adults: A Community-Based Cohort Study</p>

Abstract: Background: There was a lack of studies focusing on older adults about the longitudinal association between metabolic syndrome (MetS) and hyperuricemia (HUA). We aimed to assess the association of baseline MetS and incident HUA among older Chinese adults, with a special focus on the associations between different combinations of MetS components and HUA. Methods: Data of 3247 Chinese adults aged 60 years or older included in a communitybased longitudinal cohort study were analyzed. Anthropometric examinations a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…The association between hyperuricemia and MetS has been explored in many cross-sectional studies, but prospective studies are rare ( 7 9 , 19 , 20 ). Some studies suggest that MetS can increase the incidence of hyperuricemia ( 19 21 ); however, others suggest that hyperuricemia should be included as a component of MetS ( 7 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The association between hyperuricemia and MetS has been explored in many cross-sectional studies, but prospective studies are rare ( 7 9 , 19 , 20 ). Some studies suggest that MetS can increase the incidence of hyperuricemia ( 19 21 ); however, others suggest that hyperuricemia should be included as a component of MetS ( 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…The association between hyperuricemia and MetS has been explored in many cross-sectional studies, but prospective studies are rare ( 7 9 , 19 , 20 ). Some studies suggest that MetS can increase the incidence of hyperuricemia ( 19 21 ); however, others suggest that hyperuricemia should be included as a component of MetS ( 7 ). The latest study that reviewed the China Health and Retirement Longitudinal Study (CHARLS) data from 2011 to 2015 concluded that there is a bidirectional relationship between MetS and hyperuricemia, which is in agreement with our research ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent report from China showed that the prevalence rates of HUA increased steadily from 8.5 to 18.4% from 2000 to 2017 (4). Previous studies have suggested that lifestyle (especially diet) and history of cardiovascular disease were related to the incidence of HUA (5)(6)(7)(8). Of particular concern is that diet might be the most important and cost-effective factor that can be used to modify the risk of HUA (9).…”
Section: Introductionmentioning
confidence: 99%
“…It is defined as a cluster of disorders and risk factors for cardiovascular disease, including abdominal obesity, hyperglycemia (including impaired glucose tolerance and diagnosed diabetes), dyslipidemia, and elevated blood pressure. Many studies have demonstrated a strong association between metabolic syndrome or metabolic components and the risk for subsequent development of type 2 diabetes (4-8), cardiovascular disease (9)(10)(11)(12)(13), hyperuricemia, gout (14)(15)(16), and CKD (17)(18)(19)(20)(21). These factors interact as both cause and effect, and the multiple mechanisms involved in the development of CKD in patients with metabolic syndrome have not been well-established.…”
Section: Introductionmentioning
confidence: 99%